Maraviroc Population Pharmacokinetics Within the First 6 Weeks of Life. Issue 11 (9th August 2022) - Liyanage, Marlon; Nikanjam, Mina; McFadyen, Lynn; Vourvahis, Manoli; Rogg, Luise; Moye, John; Chadwick, Ellen G.; Jean-Philippe, Patrick; Mirochnick, Mark; Whitson, Kyle; Bradford, Sarah; Capparelli, Edmund V.; et al.
Abstract : Background: Treatment and prophylaxis options for neonatal HIV are limited. This study aimed to develop a population pharmacokinetic model to characterize the disposition of maraviroc in neonates to inform dosing regimens and expand available options. Methods: Using maraviroc concentrations from neonates who received either a single dose or multiple doses of 8 mg/kg of maraviroc in the first 6 weeks of life, a population pharmacokinetic model was developed to determine the effects of age, sex, maternal efavirenz exposure and concomitant ARV therapy on maraviroc disposition. The final model was used in Monte Carlo simulations to generate expected exposures with recommended dosing regimens. Results: A total of 396 maraviroc concentrations, collected in the first 4 days of life, at 1 week, at 4 weeks and at 6 weeks, from 44 neonates were included in the analysis. After allometrically scaling for weight, age less than 4 days was associated with a 44% decreased apparent clearance compared with participants 7 days to 6 weeks of life. There were no differences identified in apparent clearance or volume of distribution from ages 7 days to 6 weeks, sex, maternal efavirenz exposure or concomitant nevirapine therapy. Monte Carlo simulations with FDA-approved weight band dosing resulted in the majority of simulated patients (84.3%) achieving an average concentration of ≥75 ng/mL. Conclusions: While maraviroc apparent clearance is decreased in the first few days of life, the current FDA-approved maraviroc weight band dosing provides maraviroc exposures for neonates in the first 6 weeks of life, which were consistent with adult maraviroc exposure range. Maraviroc provides another antiretroviral treatment option for very young infants.